2019
DOI: 10.3390/su11247008
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Energy-Related Carbon Emissions in Inner Mongolia, China

Abstract: Inner Mongolia has shown both rapid economic growth and a large renewable energy base, this has come about by the introduction of the "Western Development" strategy and renewable energy policy of the Chinese Government. However, this has led to a contradictory situation where both high carbon emission and reduction exist together. The average economic growth of Inner Mongolia reached 15.76% between 2006 and 2016, which caused huge CO 2 emissions. However, promotion of the renewable energy policy (since 2005) r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…According to [51], for these economies, the flow of foreign direct investment (FDI) and the development of the financial market are fundamental in promoting the consumption of renewable energies, in addition to reducing emissions and promoting economic growth. The BRICS economies were also investigated in isolation: Brazil was studied by [54][55][56], Russia by [57], China and India by [58] and China by several [59][60][61][62][63][64][65], and there were also investigations for Chinese provinces such as [66,67]. Moreover, Brazil, China and the USA were studied by [68], China and USA in [69], and China, USA, France and Japan by [70].…”
Section: Discussionmentioning
confidence: 99%
“…According to [51], for these economies, the flow of foreign direct investment (FDI) and the development of the financial market are fundamental in promoting the consumption of renewable energies, in addition to reducing emissions and promoting economic growth. The BRICS economies were also investigated in isolation: Brazil was studied by [54][55][56], Russia by [57], China and India by [58] and China by several [59][60][61][62][63][64][65], and there were also investigations for Chinese provinces such as [66,67]. Moreover, Brazil, China and the USA were studied by [68], China and USA in [69], and China, USA, France and Japan by [70].…”
Section: Discussionmentioning
confidence: 99%
“…Referring to previous studies, the control variable set of this paper is shown as follows: Urbanization leads to the aggregation of human activities, increasing the volume of energy consumption and carbon emissions. Therefore, the urban population is selected as the proxy variable for the country's population size 46 . Energy consumption and carbon emissions are directly affected by a country's economic aggregate; thus, gross domestic product (GDP) is used as a proxy variable 5 .…”
Section: Methodsmentioning
confidence: 99%
“…Sun et al [23] combined the Kaya identity factor in the LMDI and IPAT models with the Tapio decoupling index method in the exponential decomposition method. In another study, Tseng [24] used the LMDI to decompose the carbon emission factors of Inner Mongolia, China, developed the decoupling index, and analyzed the factors to assess the decoupling status. On the whole, it is more common for scholars to combine the IPAT model with the LMDI in the exponential decomposition method.…”
Section: Introductionmentioning
confidence: 99%